Stars - McLure, Kirstie; Couper, Heather; Gorst, Martin; Hearle, Alex ([S.l.] : TLC Video [production company] ; [S.l.] : Discovery Channel Video, 1999)
Discover suprising facts about stars and our most valuable star, the Sun
Writer, Nigel Henbest ; editor, Raimondo Aiello
Narrator: John Hurt
Keywords: Sun; Stars; Astronomy